A segurança alimentar e nutricional em diferentes tipos de famílias brasileiras: uma análise do período de avanço entre 2004 e 2013 - Xavier, Bruno Damasceno (2024)
The topic of food and nutritional security (FNS) is gaining ground again in political and economic discussions today, largely due to the worsening of the food situation that occurred after the COVID-19 Pandemic. Data for Brazil show a significant advance in FNS between the years 2004 to 2013 (PNAD/IBGE), after this period, data from POF 2017/2018 show a rapid and profound reversal, which worsens even further with the numbers subsequent to the arrival of the pandemic (2020 and 2022 – PENSSAN network), with food and nutritional insecurity (FNI) starting to affect the majority of Brazilian people and households. The focus of this thesis is on the period of positive advancement of the SAN in Brazil, between 2004 and 2013. The literature on the period shows that the advancement of the SAN in the country is directly linked to the increase in the average disposable income of families. Furthermore, among the various factors associated with FNS, research highlights the importance of the reference person's occupation as an influence on eating conditions in households. The first question we sought to investigate was whether the FNS evolved in a homogeneous manner when we consider different types of families, based on the occupation positions of its members. To do this, we start from the hypothesis that given the importance of income, in terms of level and stability, when we consider different types of families, there would have been a heterogeneous advance, due to the different occupation positions of the members of these families. Secondly, we understand that the evolution of family income has caused them to start consuming new goods, which they previously did not have the possibility of consuming. Consequently, the increase in disposable income caused a change in families' consumption patterns, which, in turn, caused them to allocate/divert part of their monetary resources to non-food items. Therefore, as a second hypothesis, we had the idea that this income diversion may have made it difficult and created barriers for the evolution of FNS among different types of families, especially those in a situation of severe FNI. To test these hypotheses, our general objective was to gather elements, based on microdata from the PNADs (2004, 2009 and 2013), that would allow us to differentiate the manifestation of FNS between different types of families, separating for comparison those residing in rural and urban areas, in an analysis with a national focus and in a specific macro-region, in this case, the Central-West. More specifically, we aim to: i) describe and analyze the evolution of FNS levels among different types of families; ii) identify other elements that would allow us to point out differences between the types of families (“net FNS” and “new effort required”); iii) describe and analyze the evolution of different levels of FNI between types of families; iv) describe and compare the evolution of families' access to household infrastructure conditions (or services) and some consumer goods; v) gather elements from the national literature that help us understand the evolution of the FNS during the period of analysis; and vi) gather elements that allow us to visualize/describe the complexity of the FNS concept and its forms of evaluation/monitoring. For this, the methodology used was developed within the scope of the RURBANO project, differentiating/grouping 4 types of families, namely: employer families; self-employed families; employee’s families; and, non-employed families. After this grouping, we cross-referenced information from the PNADs on the different levels of FNI for each type of family and the respective access conditions of resident households to infrastructure services (garbage collection, piped water, existence of a bathroom and sewage system), in addition, family access to some consumer goods (refrigerator, stove, television, cell phone, washing machine, personal computer and internet access). In addition to this methodology, in the third chapter, we briefly present a study of the association between types of families in the Central-West and different levels of FNI, using a multinomial logit model. Among the results we can highlight strong elements that confirm our first hypothesis, with a significant heterogeneous manifestation of FNS depending on the type of family. We found that employer families have advantages in terms of FNS over other types of families in all situations (national, regional, rural, urban, agricultural and non-agricultural), on the other hand, self-employed families and families of unemployed people have the worst food conditions. In terms of the number of families in FNS, it is possible to observe that in some situations, such as in the case of self-employed families in rural areas in the Central-West, there was no increase in the number of families in this situation (FNS), there was actually a drop, but there was still a percentage increase in FNS. This is because the drop in the total number of families (denominator) was greater than the drop in the number of families in FNS (numerator). In terms of the infrastructure conditions of households, it was possible to observe a double advantage in employer families, on the one hand, some already had higher levels of access since 2004, on the other, some families were in similar conditions to the other types in 2004, however, reached much higher levels in 2013, especially among those with severe FNS. In this way, it was possible not only to confirm our first hypothesis, but also to find extreme cases of manifestation of FNI, such as the case of families of agricultural and non-agricultural employers in rural areas of the Central-West region who reached 100% of FNS in 2013, while agricultural self-employed families (family farming) in this region had a serious increase in FNI in the period of analysis. Regarding the second hypothesis tested, we observed that the evolution of access for families in severe FNI, in Brazil and in the Central-West, evolved, in percentage terms, above that of families in FNS, generating elements that allow us to conjecture that there was in fact a allocation of monetary resources for non-food goods, even among families in conditions of greater food severity, which may have hindered the evolution of FNS to higher levels. Therefore, we can conclude that the actions and public policies used in the period and, more broadly, the socioeconomic and political situation that was formed, affected the types of families in different magnitudes, causing some types of families to evolve more than others in terms of FNS. Thus, while some families reached 100% SAN, others did not leave the Hunger Map. In other words, depending on the actions taken and the current situation, different types of families are affected differently, depending on the occupation position of their members.